Rethinking Transport Infrastructure Planning to Extend Its Value over Time. (March 2020) - Givoni, Moshe; Perl, Anthony
Contemporary transport infrastructure planning typically rests upon the core belief that physical mobility has inherent advantages and that more of it will always yield better socioeconomic outcomes. Such an embrace of maximum growth yields a misguided calculus for planning transport infrastructure. Rather than seeking to meet the demand for future mobility by reflexively expanding the quantity of infrastructure, there is a need to consider alternatives that can support a sustainable future. By applying the "half-life" concept to transport infrastructure, this article explores alternatives to extending its use over time that can open up new possibilities for generating and extending its value to society.